Yes, Australia is Highly Motivated to Focus on Domestic Renewable Micro Electricity Generation for Domestic Buildings – Economy Wise - Maklad, Yasser (International Journal of Energy Economics and Policy, 2014)
In this study, an overview of energy, how Australia is producing electricity, highlighting currently used fossil fuel generation technique’s major share compared with starting renewable energy technique’s minor share of total electricity generated. How electricity transmission is done, wholesale and retail electricity pricing method and such prices movement history are presented. A focus on economic aspects presenting residential electricity sector prices and Australian households’ income and how it is affected by electricity consumption bill supplied by the traditional technique of electricity generation via coal burning widely utilized in Australia. Statistical economic indices data are presented such as consumer price index and wage price index are shown, graphed, discussed and analysed. This study concluded, it is a strong yes that Australia is highly motivated to focus on domestic renewable micro electricity generation for domestic buildings considering the historical and current ongoing economic aspects relevant to Australian households. Today it is a highly motivated and stimulated option; however, tomorrow it is an obligation. Keywords: Australian households’ income; domestic electricity consumption; electricity generation and transmission; grid connection; feed-in tariffs; renewable energy; micro electricity generation. JEL Classifications: B3; D1; D8 <!–[endif] –>